1975
DOI: 10.1111/j.1365-2389.1975.tb01947.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Freundlich Isotherm for Soil Phosphate Sorption Data

Abstract: Phosphate sorption data for twenty-nine soils were found to fit the Freundlich adsorption isotherm better if a measure of native labile P was first added to the sorption data, and this sum plotted against intensity. The exponent from the isotherm thus obtained was closely related to exchangeable A1 (in acid soils) and exchangeable Ca (in neutral and calcareous soils), with a mole ratio of one P to 6 A1 or Ca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

1980
1980
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 7 publications
3
35
0
3
Order By: Relevance
“…However, in the present study there existed quite a poor association between the water extractable Pin the soil and the term <t B corresponding to the term a of FITTER and SUTTON (1975). This result supports the concept discussed by HARTIKAINEN (1982 b) that, with increasing solution-soil ratio the isotherm expressing the P exchange as a function of final P concentration can be assumed in practice to converge the y-axis without intersecting it.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…However, in the present study there existed quite a poor association between the water extractable Pin the soil and the term <t B corresponding to the term a of FITTER and SUTTON (1975). This result supports the concept discussed by HARTIKAINEN (1982 b) that, with increasing solution-soil ratio the isotherm expressing the P exchange as a function of final P concentration can be assumed in practice to converge the y-axis without intersecting it.…”
Section: Resultssupporting
confidence: 79%
“…The equation of the isotherm B presented in this study is to some extent similar to the Freunlich sorption isotherm modified by FITTER and SUTTON (1975) into the form AP bC k a, where C stands for the P concentration in the final solution and A P the amount of sorbed P. According to the authors, the third term, a, theoretically represents the phosphate which must be removed in order to reduce P concentration in the final solution to zero, since AP = -a when C = 0. When the equation was fitted to the sorption data, a close relationship was found between a and the resin-P values, with the calcareous and acid soils falling into two distinct groups.…”
Section: Resultsmentioning
confidence: 89%
“…The particular form of the Freundlich equation that has been most often used in studies of PO 4 -P sorption to soils was originally suggested by Fitter & Sutton (1975):…”
Section: Freundlich Sorption Modellingmentioning
confidence: 99%
“…Net sorption or desorption was calculated from the changes in the DRP concentrations occurring during incubation. The P exchange by sediments was expressed as a Freundlich adsorption isotherm as modified by Fitter & Sutton (1975):…”
Section: Sorption-desorption Experimentsmentioning
confidence: 99%